Identification Level of Awareness and Knowledge of Emirati Men about HPV. (21st March 2022) - Al Shdefat, Suzan; Al Awar, Shamsa; Osman, Nawal; Khair, Howaida; Sallam, Gehan; Maki, Sara
Abstract : One of the most frequent cancers that affects males globally is cervical cancer (CC) that kills hundreds or even thousands of women each year, particularly in underdeveloped nations. The study focuses on human papillomavirus (HPV) that contributes to cervical cancer (CC) development. In the majority of Arab nations, there seems to be no public education or vaccination programs. In research, methodological rigor is employed to find solutions to both theoretical and practical difficulties. This research aims to assess the knowledge and awareness of the HPV vaccination among Emirati men. Results of the research showed that Emirati males had a poor understanding of HPV and its vaccination. According to the findings of this research, Emirati males lack a basic understanding of HPV, which necessitates the implementation of national HPV education initiatives. We have identified several critical knowledge gaps that can be filled in the future regarding HPV infection and vaccination.